2016
DOI: 10.1039/c5cs00815h
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor bonding in novel low-coordinated compounds of boron and group-14 atoms C–Sn

Abstract: A summary of theoretical and experimental work in the area of low-coordinated compounds of boron and group-14 atoms C-Sn in the last decade is presented. The focus of the account lies on molecules EL2, E2L2 and E3L3, which possess dative bonds between one, two or three atoms E and σ-donor ligands L that stabilize the atoms E through L→E donor-acceptor interactions. The interplay between theory and experiment provides detailed insight into the bonding situation of the molecules, which serves as guideline for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(92 citation statements)
references
References 119 publications
1
89
0
2
Order By: Relevance
“…All the CAAC cumulenes are in a trans conformation. PESs as af unction of the angle C1-C2-C3 were calculated while forcing the other terminal angle (C2-C3-C4 for [3]cumulenes, C3-C4-C5 for [4]cumulenes, C4-C5-> C6 for [5]cumulenes, C5-C6-C7 for [6]cumulenes, and C6-C7-C8 for [7]cumulenes) to be equal to the first one. All the other coordinates were optimized during the geometry scan.…”
Section: Computationalmethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the CAAC cumulenes are in a trans conformation. PESs as af unction of the angle C1-C2-C3 were calculated while forcing the other terminal angle (C2-C3-C4 for [3]cumulenes, C3-C4-C5 for [4]cumulenes, C4-C5-> C6 for [5]cumulenes, C5-C6-C7 for [6]cumulenes, and C6-C7-C8 for [7]cumulenes) to be equal to the first one. All the other coordinates were optimized during the geometry scan.…”
Section: Computationalmethodsmentioning
confidence: 99%
“…Carbones( CL 2 )h ave recently received considerable attention because of their interesting bondings cenarios. [1][2][3][4][5][6][7][8][9][10][11][12][13] The bonding in these compounds has been reported to consist of the s donation of the ligandsLto af ormally carbon(0) atom (L! C !…”
Section: Introductionmentioning
confidence: 99%
“…Thorough analysiso fc arbenes as "stabilizing"g roups has been tackled before, [60,[93][94][95][98][99][100][101] and therefore we will only point out the elements of these interactions that serve our cause. As said before,t he discoveryo ft he NHCs tabilized bissilylene in 2008 [67] was as tepping-stonei nt he acceptance of the dative bond in the field.…”
Section: Carbenes and Domino Dative Bonds (Ddb)mentioning
confidence: 99%
“…[3,4] It has been known that the extension from carbon to heavier group-14 ylidones EL2 with E = C to Pb called tetrylone ligands exhibits two lone pairs at E central atom in which the ligands were employed are phosphines PR3 such as PPh3 or less bulky PH3 groups. [5][6][7] Recently, experimental and theoretical investigations have shown that molecules of carbones which possess donor-acceptor bonds, can be sheltered for boron homologues (BH)L2 [8,9] and nitrogen cations (N + )L2. [10][11][12] The reaction of the carbone complex [(PPh3)2C(BH3)] with the strong Lewis acid B(C6F5)3 exposed the first complex of borenium cation BH2 + which can be secured through -and -donation in the structurally characterized complex [(PPh3)2C)(BH2) + ] and the complex is stabilized through donations of the  and -electron lone pairs of carbone ligand C(PPh3)2 into the -and orbitals of the BH2 + ligand.…”
Section: Introductionmentioning
confidence: 99%